An Analysis Of The Welfare Of Rice Farmers (Case Study: Rice Farmers In Village Tawangrejo Sub-District Pandaan Pasuruan Regency) - Christ Andy Ariaditha (Jurnal Ilmiah Mahasiswa FEB, 2017)
Agricultural sector always get the attention of "special" in an effort to build public welfare. Where agriculture becomes more meaningful in light of the three underlying reasons. First the agricultural sector is expected to provide sufficient food for the entire population, both the agricultural sector is seen as one of the labour camp container, the third agricultural sector is expected to provide a substantial contribution to the business of foreign exchange through exports. The third argument can at least describe fully how exactly the position and role of the agricultural sector to the economic structure of IndonesiaFrom the results of this study it can be concluded that the factors that encourage the community to conduct agricultural activities in the area of Tawangrejo village are land ownership factor, farming experience, income, the number of dependents, age and education. Education is quite high. Farmers in the village of Tawangrejo have a high level of education and they also send their children to a high enough level. For example at the undergraduate level. There are also those at the diploma level. It shows that the villagers of Tawangrejo have a high level of education even though most of the people work as farmers Health is also quite high. because people in tawangrejo village have good health. That's because the villagers consume food that is good enough and meet the nutrients of 4 healthy 5 perfect. Keywords: Welfare, welfare aspect, & rice farmers